Birth Defects and Long-Term Neurodevelopmental Abnormalities in Infants Born During the Zika Virus Epidemic in the Dominican Republic. Issue 1 (5th January 2021) - Pimentel, Raquel; Khosla, Shaveta; Rondon, Josefina; Peña, Farah; Sullivan, Gwyneth; Perez, Martha; Mehta, Supriya D.; Brito, Maximo O.
Background: When acquired during pregnancy, Zika virus (ZIKV) infection can cause substantial fetal morbidity, however, little is known about the long-term neurodevelopmental abnormalities of infants with congenital ZIKV exposure without microcephaly at birth. Methods: We conducted a cross sectional study to characterize infants born with microcephaly, and a retrospective cohort study of infants who appeared well at birth, but had possible congenital ZIKV exposure. We analyzed data from the Dominican Ministry of Health's (MoH) National System of Epidemiological Surveillance. Neurodevelopmental abnormalities were assessed by pediatric neurologists over an 18-month period using Denver Developmental Screening Test II. Results: Of 800 known live births from 1, 364 women with suspected or confirmed ZIKV infection during pregnancy, 87 (11%) infants had confirmed microcephaly. Mean head circumference (HC) at birth was 28.1 cm (SD ± 2.1 cm) and 41% had a HC on the zero percentile for gestational age. Of 42 infants with possible congenital ZIKV exposure followed longitudinally, 52% had neurodevelopmental abnormalities, including two cases of postnatal onset microcephaly, during follow-up. Most abnormalities resolved, though two infants (4%) had neurodevelopmental abnormalities that were likely associated with ZIKV infection and persisted through 15–18 months. Conclusions: In the DR epidemic, 11% of infants born to women reported to the MoH with suspected or confirmed ZIKV during pregnancy had microcephaly. Some 4% of ZKV-exposed infants developed postnatal neurocognitive abnormalities. Monitoring of the cohort through late childhood and adolescence is needed.